Sumber Informasi Orang Tua Siswa Sekolah Dasar tentang Pencegahan Kekerasan Seksual pada Anak - Rachma Noer Fadhilah; Tetti Solehati; Sukmawati Sukmawati (JANACITTA, 2025)
Abstract Child sexual abuse (CSA) in Indonesia remains a serious issue, with the number of cases continuing to rise. One of the causes of CSA is the lack of exposure to information among parents, compounded by the perception that the topic is taboo. Parents need to obtain adequate information to educate their children about preventing CSA. Information can be accessed from various sources, such as individuals, conventional media, and social media. This study aims to identify the sources of information about CSA prevention that parents utilize. The research was conducted in October 2024 using a descriptive quantitative research design with a sample of 100 parents of students in grades 1–6 at elementary schools in the Dayeuhkolot subdistrict, Bandung Regency. The sampling technique employed was stratified random sampling. The instrument used was a questionnaire developed by Solehati, (2022) titled "Prevention of Sexual Violence in Elementary School-Aged Children Involving the Role of Parents and Teachers in West Java," which includes demographic data and information sources. Data collection was conducted through Google Forms. Data analysis consisted of frequency distribution and percentages of the information sources used by parents, presented in graphical form.  The results showed that almost all respondents (88%) used social media as a source of information about CSA prevention. To develop CSA prevention programs, healthcare workers and teachers are advised to incorporate the use of social media to enhance CSA prevention efforts among parents. Abstrak Kekerasan seksual pada anak (KSA) di Indonesia saat ini masih menjadi masalah serius dengan jumlah kasus yang terus meningkat. Salah satu penyebab terjadinya KSA karena orang tua kurang terpapar informasi disertai adanya anggapan tabu. Orang tua harus mendapatkan informasi yang memadai agar dapat memberikan edukasi tentang pencegahan KSA. Informasi dapat diakses dari berbagai sumber seperti manusia, media konvensional, dan media sosial. Penelitian ini bertujuan untuk mengidentifikasi sumber informasi pencegahan KSA yang didapatkan orang tua. Penelitian ini dilakukan pada bulan Oktober 2024 menggunakan desain penelitian deskriptif kuantitatif dengan sampel orang tua siswa kelas 1-6 berjumlah 92 orang di Sekolah Dasar wilayah Dayeuhkolot Kabupaten Bandung. Teknik pengambilan sampel menggunakan stratified random sampling. Instrumen menggunakan kuesioner yang dibuat oleh Solehati, (2022) tentang “Pencegahan Kekerasan Seksual pada Anak Usia Sekolah Dasar dengan Melibatkan Peran Orang tua dan Guru Sekolah di Jawa Barat” yang berisi data demografi serta sumber informasi. Teknik pengumpulan data melalui Google Form. Analisis data berupa distribusi frekuensi dan persentase sumber informasi orang tua yang disajikan dalam bentuk grafik. Hasil penelitian menunjukkan hampir seluruh responden (88%) menggunakan media sosial sebagai sumber informasi tentang pencegahan KSA. Untuk mengembangkan program pencegahan KSA petugas kesehatan dan guru disarankan melibatkan penggunaan media sosial dalam meningkatkan upaya pencegahan KSA pada orang tua.